Empowering Urban Women in Amrit Kaal: Shgs as Agents of Change in Indian Cities - R. Kolte, Janhavi; Mapuskar, Minal (Journal of Neonatal Surgery, 2025)
The concept of Amrit Kaal heralds a new era of growth, innovation, and empowerment for India, emphasizing sustainable development, economic progress, and social transformation. Within this context, Self-Help Groups (SHGs) have emerged as key drivers of women’s empowerment, especially in rapidly urbanizing cities. These grassroots organizations, which promote collective action and mutual support, are increasingly recognized as powerful agents of change for urban women who face unique challenges in the face of urbanization, social inequality, and economic disparities. This paper explores the role of SHGs in empowering urban women during Amrit Kaal, focusing on their contribution to fostering economic independence, social cohesion, and enhanced decision-making power. As cities expand, women often find themselves marginalized due to limited access to resources, employment opportunities, and social networks. SHGs offer urban women a platform to overcome these barriers by facilitating access to credit, skill development, and social support. By pooling resources, sharing knowledge, and advocating for policy change, these groups enable women to gain financial independence, improve their livelihoods, and challenge traditional gender norms. In the Amrit Kaal era, SHGs are not only instrumental in economic empowerment but also play a pivotal role in addressing social issues such as health, education, and gender-based violence. Moreover, they contribute to fostering a sense of community and solidarity among women in urban spaces, helping to create a more inclusive and equitable urban environment.Through an analysis of case studies and empirical data, this paper underscores the transformative potential of SHGs in shaping the future of urban women. It argues that in the rapidly urbanizing cities of India, SHGs are crucial agents of change, empowering women to fully participate in the country’s socio-economic growth.